Reducing Student Tardiness Through Group Guidance With Behavior Contract Technique: Mengurangi Keterlambatan Siswa Melalui Bimbingan Kelompok Dengan Teknik Kontrak Perilaku - Anggraini, Nurdelita; Hasibuan, Ali Daud (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Punctuality is a vital aspect of student discipline, directly influencing academic engagement and school climate.Specific Background: However, recurring tardiness remains a persistent behavioral issue among high school students. Knowledge Gap: Limited empirical studies have evaluated structured group counseling interventions, particularly behavioral contract techniques, in addressing this issue. Aim: This study aims to assess the effectiveness of group guidance services based on behavioral contract techniques in reducing tardiness among students at SMA Negeri 1 Bangun Purba. Method: Utilizing a quantitative approach with a one-group pretest-posttest pre-experimental design, eight purposively sampled students from a population of 348 were assessed using a validated and reliable tardiness questionnaire. Results: Findings revealed a significant decrease in average tardiness scores from 89.9 (pretest) to 35 (posttest), supported by the Wilcoxon Signed-Rank Test with a significance value of 0.012 (p < 0.05). Novelty: This study provides concrete evidence on the application of behavioral contracts within a group guidance framework as an effective method for behavior modification in school settings. Implications: The results suggest that integrating behavioral contract strategies into counseling services can enhance students’ time discipline and foster a more conducive school environment. Highlights: Measures the impact of behavioral contracts on student punctuality. Demonstrates statistically significant reduction in tardiness. Supports counseling interventions for school discipline enhancement. Keywords: Behavioral Contract, Group Guidance, Student Tardiness, Discipline Improvement, Pre-Experimental Design